PENGARUH PEMBERIAN PUPUK UREA DAN PUPUK ORGANIK CAIR ELANG BIRU TERHADAP PERTUMBUHAN BIBIT KARET PB 260 (HEVEA BRASILIENSIS L.) - Kristianus dan Hery Sutejo (Universitas 17 Agustus 1945 Samarinda, 2014)
Effect of Urea and Elang Biru Liquid Organic Fertilizer on the Growth of Rubber Seedling (Hevea brasiliensis L.), 260 Pb variety. The objective of research were: (1) to study the effect of Urea and Elang Biru liquid organic fertilizer on the growth of rubber seedling PB 260; and (2) to find the proper combination of Urea and Elang Biru liquid organic fertilizer for better rubber seedling growth. The research lasted for about four months, from March to June 2013, it carried out at Melapeh Baru Village, Linggang Bigung Sub-District of West Kutai District, the East Kalimantan Province. It employed the Completely Randomised Design, consisted of two factors and five replications. The first factor was Urea (N), consisted of three levels: no urea application (n0), 5 g polybag-1 (n1), and 10 g polybag -1 (n2). The second factor was Elang Biru liquid organic fertilizer consentration (E) with three levels: no application (e0), 4 ml 1-1 water (e1), and 6 ml 1 -1 water (e2). Result of the research indicated that: (1). The Urea application did not affect significantly on the seedling height, stem diameter and leave number at 4, 5, and 6 months old; (2) Elang Biru liquid organic fertilizer application did not also affect significantly on the seedling height, stem diameter and leave number at 4, 5, and 6 months old;; (3) The interaction between Urea and Elang Biru liquid organic fertilizer did not affect significantly on all parameters observed. The interaction between Urea 10 g polibag-1 and 6 ml 1-1 water Elang Biru liquid organic fertilizer treatment gave the best effect for rubber seedling growth.